Antimicrobial activities of the methanol extract, fractions and compounds from Ficus polita Vahl. (Moraceae) - Ambassa Pantaleon; Poumale Herve MP; Ngameni Bathelemy; Sandjo Louis P; Kamga Justin; Kuete Victor; Ngadjui Bonaventure T (BMC, 2011)
Abstract Background Many plants of the family Moraceae are used in the treatment of infectious diseases. Ficus polita Vahl., an edible plant belonging to this family is used traditionally in case of dyspepsia, infectious diseases, abdominal pains and diarrhea. The present work was designed to assess the antimicrobial activity of the methanol extract from the roots of F. polita (FPR), as well as that of its fractions (FPR1-5) and two of the eight isolated compounds, namely euphol-3-O-cinnamate (1) and (E)-3,5,4'-trihydroxy-stilbene-3,5-O-β-D-diglucopyranoside (8). Methods The liquid microdilution assay was used in the determination of the minimal inhibitory concentration (MIC) and the minimal microbicidal concentration (MMC), against seven bacterial and one fungal species. Results The results of the MIC determination showed that the crude extract, fractions FPR1, FPR2 and compound 8 were able to prevent the growth of the eight tested microorganisms. Other samples showed selective activity. The lowest MIC value of 64 μg/ml for the crude extract was recorded on 50% of the studied microbial species. The corresponding value for fractions of 32 μg/ml was obtained on Salmonella typhi, Escherichia coli and Candida albicans ATCC strains. The MIC values recorded with compound 8 on the resistant Pseudomonas aeruginosa PA01 strain was equal to that of chloramphenicol used as reference antibiotic. Conclusion The obtained results highlighted the interesting antimicrobial potency of F. polita as well as that of compound 8, and provided scientific basis for the traditional use of this taxon in the treatment of microbial infections.